Six1 is down‐regulated in end‐stage human dilated cardiomyopathy independently of Ezh2. (22nd January 2015) - Tschirner, Anika; Palus, Sandra; Hetzer, Roland; Meyer, Rudolf; Anker, Stefan D.; Springer, Jochen
Abstract : Background: Recently, it was shown that a knock‐out (KO) of the polycomb histone methyltransferase Ezh2 leads to cardiac hypertrophy in mice, which was driven by the homeodomain transcription factor Six1. Here, we analyzed the expression of Six1 and its regulating factor Ezh2 in cardiac tissue of patients with end‐stage dilative cardiomyopathy (DCM). Methods: Tissue samples of patients with end‐stage DCM ( n  = 35) were compared with controls ( n  = 12) for the protein expression of Ezh1, Ezh2, Six1, and a marker of protein expression p70S6K. Results: Contrary to the Ezh2‐KO mouse model, we found a down‐regulation of Six1 (26%) and an up‐regulation of Ezh2 (76%) in DCM hearts, (both P  < 0.05). Expression of Ezh2 and Six1 did not correlate in human tissue (DCM: r 2 : 0.03, P  = 0.31 and donor: r 2 : 0.05, P  = 0.45). Expression of Six1 weakly correlated with left ventricular end‐systolic diameter and fractional shortening. In DCM, Six1 also showed a positive correlation to the expression of the ribosomal protein p70S6K ( r : 0.39, P  = 0.029), which is involved in protein synthesis. This correlation was not seen in donor tissue, which showed a trend for a negative correlation ( r : −0.49, P  = 0.08). Conclusion: Our data indicate that the Ezh2/Six1 axis might be involved in human DCM. However, Six1 expression may be regulated by factors other than Ezh2, and more research is needed to determine the precise role of Ezh2/Six1 in human DCM.